2019
DOI: 10.1101/2019.12.20.884932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transfer Learning for Predicting Conversion from Mild Cognitive Impairment to Dementia of Alzheimer’s Type based on 3D-Convolutional Neural Network

Abstract: Dementia of Alzheimer's Type (DAT) is associated with a devastating and irreversible cognitive decline. As a pharmacological intervention has not yet been developed to reverse disease progression, preventive medicine will play a crucial role for patient care and treatment planning. However, predicting which patients will progress to DAT is difficult as patients with Mild Cognitive Impairment (MCI) could either convert to DAT (MCI-C) or not (MCI-NC). In this paper, we develop a deep learning model to address th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…The standard perturbation method has been widely used in the study of Alzheimer's disease [32,48,45,37] and related symptoms (amyloid-β pathology) [49]. However, most of the time, authors do not train their model with perturbed images.…”
Section: Perturbation Methods Applied To Neuroimagingmentioning
confidence: 99%
“…The standard perturbation method has been widely used in the study of Alzheimer's disease [32,48,45,37] and related symptoms (amyloid-β pathology) [49]. However, most of the time, authors do not train their model with perturbed images.…”
Section: Perturbation Methods Applied To Neuroimagingmentioning
confidence: 99%
“…Therefore, some studies suggested a strategy used to address the classification of sMCI and pMCI classes, which is to employ a pretrained network trained on diverse cohorts, including CN, and AD to predict whether or not people with MCI will convert to AD. [14][15][16] Basaia et al 14 used a 3D convolutional neural network (3D CNN) based on a single cross-sectional sMRI to predicate MCI to AD conversation. In addition, this study investigated the limitations of using a single-center dataset.…”
Section: Impact Statementmentioning
confidence: 99%
“…The CNN-EL model achieved a 62.0% accuracy in distinguishing patients with MCI converters from those who will remain stable. Bae et al 16 used a CNN model that was first trained on sMRI scans of healthy individuals and those with AD to predict which individuals with MCI converted (MCI-C) and which did not convert (MCI-NC). Researchers used a classification task of NC versus AD as the source task for transfer learning to the target task, which is MCI-C versus MCI-NC.…”
Section: Impact Statementmentioning
confidence: 99%
See 2 more Smart Citations